Study Of Non-Performing Asset (Npa) Mitigation Practices In Co- Operative Banks In Thane, Maharashtra, India - PETHE, DR. AJAY W.; CHIMNANI, DR. KIRAN (The journal of contemporary issues in business and government, 2021)
Non-Performing Assets (NPA) refers to the categorization of Credit/ loans or advances in the books of a lender (financial institutions/banks) in which there is no payment of interest and principal have been made and are “past due” for a specified period of time. NPA is employed by financial institutions that ask loans that are in jeopardy of default. There is no doubt that increasing NPA has become a matter of concern for any bank or financial institution whether it is commercial or co-operative. There are instances where many co-operative banks have faced strict action and closure from the central bank. The present paper is an attempt to study and analyze the causes of NPA in selected co- operative banks in Thane. It studies the causes of NPA at the micro level for co-operative banks and brings out the main causes liable for assets turning into non- performing. This paper further highlights the importance of NPA in Credit risk management mitigation in Cooperative banks in Thane. The findings of this paper will significantly contribute to the effective asset allocation to cooperative bank and help them to grow and succeed.